Formation of Nonwoven Webs with Electrostatic Field Effect - Kanah, Ahmad S.; Turkawi, Mohamed (Al-Nahrain Journal for Engineering Sciences, 2020)
The non-woven materials industry is one of the fastest-growing industries in the world with the ability to produce materials in less time, specifications, and better prices. nonwoven materials are defined as a web of guided or random fibers that are bonded by friction, interlacement or adhesion. In this research, the rotary electrospinning system was used and a prototype was made to study the process and the complete visualization in terms of the correlation of the electrostatic forces to the formation of nanofibers by preparing polymeric solutions and exposing them to the electric field between the positive electrode (the serrated cylinder) and the Grounded electrode (plate) and produced high-precision fibers with a diameter (185nm) at 25 kV, whereas the installation of polyvinyl alcohol (PVA) was with different concentrations and the formed fibers possessed an effective surface and deposited on a collector electrode forming nonwoven webs and high productivity is the most important feature of this system compared with the traditional electrospinning system.